1998
DOI: 10.3171/jns.1998.88.6.0943
|View full text |Cite
|
Sign up to set email alerts
|

Surgical experience with an implanted artificial cervical joint

Abstract: The use of stainless steel in the cervical spine appears to be suitable for this joint replacement design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
115
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(118 citation statements)
references
References 6 publications
0
115
0
3
Order By: Relevance
“…In a small case series, Cummins et al 5 demonstrated that cervical arthroplasty was safe, effective, and preserved segmental motion. Recently, the 5-year outcomes for the Prestige ST (Medtronic Sofamor Danek) were presented showing improved outcomes for patients receiving a TDR versus an ACDF.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a small case series, Cummins et al 5 demonstrated that cervical arthroplasty was safe, effective, and preserved segmental motion. Recently, the 5-year outcomes for the Prestige ST (Medtronic Sofamor Danek) were presented showing improved outcomes for patients receiving a TDR versus an ACDF.…”
mentioning
confidence: 99%
“…13,16 Several case series have demonstrated that multilevel cervical arthroplasty for the treatment of radiculopathy and myelopathy can be an alternative with good outcomes. 5,15 In a prospective study, Pimenta et al 14 demonstrated that multilevel cervical arthroplasty had improved outcomes over singlelevel arthroplasty. Several clear advantages to performing multilevel cervical arthroplasty are preserved motion, decreased adjacent-level biomechanical stressors, and potentially better outcomes.…”
mentioning
confidence: 99%
“…Unfortunately, fusion surgery has been reported to increase the biomechanical stresses at the adjacent segments, which could lead to further degenerative symptomatic disc disease at the adjacent levels. 4,6 An alternative approach to cervical fusion surgery is to restore motion to the diseased segment with disc arthroplasty. The goal of the disc prosthesis is to replace the diseased disc while preserving and/or restoring the motion at the treated spinal level.…”
mentioning
confidence: 99%
“…2). Cummins, et al, 10 reported on 20 patients who were followed for a mean of 2.4 years. Patients with radiculopathy improved, and those with myelopathy either improved or their symptoms stabilized.…”
Section: Cervical Arthroplastymentioning
confidence: 99%
“…2,4,5,13,21,26,38,41,55 The results of a cervical disc prosthesis, which was originally developed in Bristol, England, have been reported. 10 The second-generation Cummins disc is a ball-andtrough-type device constructed of stainless steel. It is secured to the vertebral bodies with solid screws.…”
Section: Cervical Arthroplastymentioning
confidence: 99%